Evaluation of industrial wastes in wheat (Triticum aestivum)-maize (Zea mays) cropping system in mid-hills sub-humid zone of Himachal Pradesh - MAHAJAN, K K; KUMAR, SANJAY; DEV, S P; BHARDWAJ, K K R; GUPTA, S P (The Indian Journal of Agricultural Sciences, 2014)
A 3-year field experiment was conducted at Bajaura, Himachal Pradesh, to evuluate the effciency of industrial wastes, viz biological sludge, residue from the medicinal plants and farmyard manure, for enhancing yield of wheat (Triticum aestivum L. emend. Fiori & Paol.maize (zea mays L.) cropping system. The biological sludge resulted in 16.5 and 30% higher yield of wheat than farmyard manure and the control respectively. The residue from medicinal plant:; was at par with farmyard manure, but both were significantly superior by 10.0-11.5% to the control. There was a significant interaction between organic materials and nitrogen levels during all the years. The pooled maize grain yield through biological sludge + 30 kg N/ha was similar to the yield obtained by applying farmyard manure + 90 kg N/ha and thus resulting a saving of 60 kg N/ha.